Guest satisfaction level towards bartender services at the Melia Bali Hotel’s Tapas Bar - G. Wahyu Putra Perdana; Ida Ayu Elistyawati; I Made Darma Oka; I Ketut Astawa; Gede Ginaya (Politeknik Negeri Bali, 2021)
The purpose of this study was to determine the level of guest satisfaction with bartender services and efforts made by bartenders to increase guest satisfaction at the Melia Bali Hotel’s Tapas Bar. Data was obtained by distributing questionnaires that have been tested for validity and reliability, with a total sample of 60 respondents. Then, the data is processed with service quality techniques and important performance analysis presented with Cartesian diagram. The result showed that guest satisfaction with bartender services the Melia Bali Hotel’s Tapas Bar as a whole has shown good service as indicated by the gap of service quality scores. The result of the important performance analysis show more positive service quality gap scores than negative service quality scores.